Makna Bangunan Rumah Adat Lontiok Masyarakat Melayu Kuok: Kajian Semiotik - Redovan Jamil; Hasnah Faiza; Elmustian Elmustian; Syafrial Syafrial (Journal on Education, 2023)
This study aims to explain the form and social meaning of the Lontiok House in Kampar District, Pulau Belimbing Village. The Lontiok house has a unique/traditional architecture because of its patterns and ornaments in the form of carvings so that its splendor can be seen even more. The characteristics and colors of the ornaments of the Lontiok House depict the life and daily personality of the Malay people, which are thick with customs that must be upheld and the Islamic religion which is firmly applied in everyday life. This paper identifies and documents this house as one of the Malay buildings that needs to be maintained and preserved and has a social meaning that is adhered to by the people there. A qualitative research method with a field study approach was used in this study because the research object was directly reviewed in the field. Theories about Malay architecture and Malay building ornaments serve as background knowledge supported by information obtained from literature and field data as well as actors within the scope of research. The results of this study indicate that the existence of the Lontiok House building has its own function, form and meaning related to people’s lives in Pulau Belimbing Village, Kampar District.